The Areal Pattern of Burned Tree Vegetation in the Subarctic Region of Northwestern Canada - Timoney, K.P.; Wein, Ross W. (ARCTIC, 1991)
Vegetation and terrain analyses of 1312 air photos spanning the subarctic, low arctic, and portions of the adjacent high boreal region of northwestern Canada permitted geographic characterization of the areal pattern of burned forest and forest-tundra vegetation. In terms of its lower areal extent of burns, and lower frequency of air photos showing burns, the forest-tundra is distinct from both open crown and closed crown forest regions. Burns show a general decrease in areal coverage from the northwest (Mackenzie River to Great Bear Lake: 0-50% of the terrain) to the southeast (Great Slave Lake to Hudson Bay: 0-10%). In the northwest, the flat till plains, high cover of continuous mature forest, and scarcity of lakes, coupled with dominance of slowly regenerating white spruce (in the forest-tundra) may help to account for the extensive burned vegetation. In the eastern half of the study region, the northern limit of burns normally does not extend beyond the line where tree cover equals upland tundra cover. In this eastern sub-region, tree cover decreases rapidly northward within the southern half of forest-tundra, constraining the areal extent of individual burns. Burns extend about 25-75 km into the forest-tundra, decreasing in areal coverage with distance east of Great Slave Lake. Burn cover in the forest-tundra north of Great Slave Lake generally exceeds that east of Great Slave Lake. Weather patterns and an abundance of lakes may help to account for the lower cover of burns east of Great Slave Lake. Burns north of Great Slave Lake peak in cover in the low Subarctic along a NW-SE axis that lies NE of high fire risk and occurrence zones. Strong correlations were observed between burn cover and upland tundra cover (-r) and between burn cover and the tree:upland tundra cover ratio (+r).Key words: boreal, climate, fire ecology, Northwest Territories, spruce, Subarctic, vegetation, weather Mots clés: boréale, climat, écologie du feu, Territoires du Nord-aa-Ouest, épinette, Subarctique, végétation, climat